Clinical Profile Management of Liver Abscess with Percutaneous Pigtail Cathater - Honeypalsinh H. Maharaul; Vimal Vora; Ketul Shah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Management of liver abscess has advanced in this era with many patients wanting its nonsurgical treatment. Percutaneous drainage with Ultrasound guidance is one such minimal invasive procedurefor management of abscess with its own limitation and advantages. We have undertaken this study at ourinstitute to study clinical profile and management of liver abscess.Methodology: All the patient enrolled after taking detailed history and Ultrasound was done. After givingconsent an ultrasound guided pigtail catheter was insertion was done under local anesthesia. Post procedureall the parameters were observed and antibiotics was given and depending upon drainage of pus patientswere followed.Results: Total 30 patient of liquefied and partially liquefied liver abscess were enrolled in this study. Underlocal anesthesia ultrasound guided pigtail catheters of various sizes (14 F) were introduced in these patientsusing the Seldinger technique. There were 25 male and 5 female patients in this study.Most commonaffected age group was 31-40. Abdominal pain with fever was common presenting features. All the patientsrecovered in this study.Conclusion: Ultrasound guided percutaneouspigtail catheter drainage ofliver abscesses is cost effective andminimal invasive procedure for liquefied and partially liquefied abscesses.